Extensive Macular Atrophy with Pseudodrusen Imaged with OCT Angiography - Jaclyn L. Kovach (Case Reports in Ophthalmological Medicine)
This report describes the first case of extensive macular atrophy with pseudodrusen (EMAP) imaged with optical coherence tomography angiography (OCTA). A 58-year-old Caucasian man presented with decreased central vision in both eyes. Fundus examination showed large areas of macular atrophy centered on the fovea surrounded by diffuse reticular pseudodrusen. Spectral domain OCT (SDOCT) revealed outer retinal and choriocapillaris atrophy. OCTA demonstrated marked absence of choriocapillaris flow. Extensive macular atrophy with pseudodrusen is a rare clinical entity and a new extreme phenotype of macular degenerations that could shed more light on the role of pseudodrusen and choriocapillaris compromise in the pathogenesis of AMD.